Recycled duvets for building thermal insulation. (September 2020) - Bourguiba, Amel; Touati, Karim; Sebaibi, Nassim; Boutouil, Mohamed; Khadraoui, Fouzia
Abstract: This study aims to valorize duvet waste notably polyester and duck feathers in the conception of thermal insulation for buildings. Physical properties of these waste materials were investigated and mini-prototypes were designed by varying the components. Thermal conductivity tests showed that those manufactured with polyester and duck feathers have approximately the same thermal conductivity which is around 0.05 W/(m∙K). However, fire reaction tests demonstrated that polyester has a better fire behavior than duck feathers which produce a larger amount of ignited debris. Thus, the mini-prototype based on polyester was selected for full-scale reproduction and characterization. To do so, a Hot Box system was designed and developed. The full-scale tests confirmed the interesting thermal properties of the polyester, already obtained at a reduced scale. Highlights: Duvet waste valorisation in the conception of thermal insulation for buildings. Polyester mini-prototypes have a thermal conductivity and fire behavior relatively close to that marketed insulating. Recycled polyester can be considered as a thermal insulating material in the building sector.